1990
DOI: 10.1007/bf01316317
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis inPyrosoma atlanticum (Tunicata: Thaliacea: Pyrosomatida): Implications for tunicate phylogeny

Abstract: Abstract. Colonies of Pyrosoma atlanticum were collected by submersible in October 1988 in the Caribbean Sea, and testes were studied by electron microscopy. Spermatogonia, spermatocytes and early spermatids have two centrioles. The proximal centriole subsequently disappears, its remains apparently persisting in the spermatozoon as dense material adjacent to the distal centriole, which gives rise to the axoneme. At the tip of early spermatids are several 50 nm proacrosomal vesicles, which disappear leaving no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 43 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…This derivation appears improbable as the doliolids are pelagic, selection pressure for the maintenance of a planktonic larva is diminished, and it seems unlikely that a neotenic organism could have arisen from a larval form in process of decline. Additionally, comparative sperm morphology does not support the view that doliolids gave rise to the larvaceans (Holland 1990). Results of ultrastructural studies on sperm and spermatogenesis are compatible with the belief that the four pelagic tunicate groups arose independently from ascidian-like predecessors (Holland 1989(Holland , 1990.…”
Section: Larvaceamentioning
confidence: 53%
See 2 more Smart Citations
“…This derivation appears improbable as the doliolids are pelagic, selection pressure for the maintenance of a planktonic larva is diminished, and it seems unlikely that a neotenic organism could have arisen from a larval form in process of decline. Additionally, comparative sperm morphology does not support the view that doliolids gave rise to the larvaceans (Holland 1990). Results of ultrastructural studies on sperm and spermatogenesis are compatible with the belief that the four pelagic tunicate groups arose independently from ascidian-like predecessors (Holland 1989(Holland , 1990.…”
Section: Larvaceamentioning
confidence: 53%
“…Additionally, comparative sperm morphology does not support the view that doliolids gave rise to the larvaceans (Holland 1990). Results of ultrastructural studies on sperm and spermatogenesis are compatible with the belief that the four pelagic tunicate groups arose independently from ascidian-like predecessors (Holland 1989(Holland , 1990. The sperm of the Larvacea among the pelagic groups display the most plesiomorphic (primitive) features; they contrast with those of other pelagic tunicates in having a compact, rounded rather than elongated head, a distinctly demarcated midpiece, and a fully functional acrosome .…”
Section: Larvaceamentioning
confidence: 71%
See 1 more Smart Citation
“…Nielsen 1995). Recently, several lines of evidence support the view that appendicularians represent the group that diversified earliest among the five distant classes of tunicates (Holland 1989(Holland , 1990Holland and Holland 1989;Wada and Satoh 1994;Wada 1998;Nishino et al 2000;Swalla et al 2000). These results imply that, in order to define the ancestral characters of chordate bodies, understanding the tailed body plan of appendicularians, which may be directly comparable to those of other chordates, is indispensable.…”
Section: Introductionmentioning
confidence: 81%
“…According to the recent morphological and molecular phylogenetic analyses, it is most likely that the ancestral stock of tunicates initially diverged the group of appendicularians (Haeckel 1868;Brooks 1893;Tokioka 1971;Holland and Holland 1989;Holland 1989Holland , 1990Wada and Satoh 1994;Wada 1998;Swalla et al 2000), although the analysis on the 18S rDNA data set indicated that the position of appendicularians leaves ambiguity because of the relatively high rate of genetic changes in their sequences Swalla et al 2000). Some studies have suggested the tailed freeswimming, not sessile, organism as the ancestor of tunicates (Wada 1998;Nishino et al 2000;Swalla et al 2000).…”
Section: Comparative Morphology Of Tunicate Notochordmentioning
confidence: 94%